Cerai Lebe sebagai Inisiatif Lokal dalam Upaya Meminimalisir Praktek Perceraian Liar (Studi Kasus di Desa Cangkring Kabupaten Indramayu) - Nuroniyah, Wardah (Fakultas Syariah IAIN Purwokerto, 2020)
There are a lot of divorces conducted outside the court that occurs in Cangkring Village, Indramayu Regency. Uniquely in this village Lebe (a marriage registrar officer) became a facilitator in matters of divorce including in terms of handling administratively the data of divorced couples without submitting to the Religious Courts. Through a socio-juridical study, it is understandable as a choice for the community in resolving conflicts in marriages. There are many reasons for choosing divorce by Lebe, the individual reasons, such as the geographical location of the village that far from the court, economic factors, early marriage, low human resources, or local socio-cultural conditions that affect a person to do divorce through the Lebe. Based on the theory of social action by Talcott Parsons, the actors who chose divorce through Lebe are considered easier to achieve its goal of divorce. Divorce by Lebe in Cangkring village is intended to curb peace and legal protection for the people who have a very high divorce rate. The community was given convenience because the rules in divorce are not as complicated as the divorce process in the Religious Court, even though it is considered illegal.